2017
DOI: 10.1007/s40097-017-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of palladium nanoparticles supported on active carbon for synthesis of disproportionate rosin (DPR)

Abstract: Disproportionate rosin (DPR) is a mixture of rosin acids with dehydro-abietic acid as its major component. Alkaline salts of DPR are used as emulsifier surfactant in emulsion polymerization reactions. In this work, synthesis of DPR by the use of palladium nanoparticles loaded on activated carbon was studied. The nanocatalyst was characterized by TEM, SEM, XRD, N 2 adsorptiondesorption and AAS. The reusability of the prepared nanocatalyst was successfully examined three times with only a very slight loss of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
0
4
0
1
Order By: Relevance
“…Here in, the catalytic activity of Fe 3 O 4 -Pd-C in the synthesis of DPR from gum rosin was studied, and the reaction was checked by gas chromatography (GC) analysis [13]. A control experiment showed that Fe 3 O 4 and Fe 3 O 4 -active carbon could not catalyze this disproportionation reaction, and the presence of palladium is essential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here in, the catalytic activity of Fe 3 O 4 -Pd-C in the synthesis of DPR from gum rosin was studied, and the reaction was checked by gas chromatography (GC) analysis [13]. A control experiment showed that Fe 3 O 4 and Fe 3 O 4 -active carbon could not catalyze this disproportionation reaction, and the presence of palladium is essential.…”
Section: Resultsmentioning
confidence: 99%
“…In our recently efforts, we have found that the activated carbon-supported palladium nanoparticles are an efficient nanocatalyst for the disproportionation of rosin [13]. Here in, the catalytic activity of magnetic palladium-carbon for disproportionation of rosin is reported.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Disproportionated rosin adalah campuran dari dehydroabietic acid dan dihydroabietic acid serta campuran sedikit asam rosin lainnya [3]. Disproportionated rosin pada industri digunakan sebagai pengemulsi dalam produksi karet sintetis, bahan peracikan untuk karet, dan sebagai bahan baku pembuatan rosin sintetis.…”
Section: Pendahuluanunclassified
“…It is important to mention here that isomerization of levopimaric acid and neoabietic acid into abeitic acid followed by auto-oxidation to DAA was observed in Chloroform-d after a certain time (6 hours). Several investigations have been made for the transformations of individual component resin acids during rosin disproportionate (Fleck and Palkin 1937;Fleck and Palkin1938;Mostafalu et al, 2017)…”
Section: X: Ppmmentioning
confidence: 99%